2022
DOI: 10.1155/2022/8268067
|View full text |Cite|
|
Sign up to set email alerts
|

A Hyperglycemic Microenvironment Inhibits Tendon-to-Bone Healing through the let-7b-5p/CFTR Pathway

Abstract: Background. Tendon-to-bone healing is a difficult process in treatment of rotator cuff tear (RCT). In addition, diabetes is an important risk factor for poor tendon-to-bone healing. Therefore, we investigated the specific mechanisms through which diabetes affects tendon-to-bone healing by regulating the Cystic Fibrosis Transmembrane Conductance Regulator (CFTR). Methods. Tendon-derived stem cells (TDSCs) were extracted from rats after which their proliferative capacities were evaluated by the MTT assay. The ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…MicroRNAs (miRNAs) belong to a family of non-coding RNAs of 20-24 nucleotides in length. MiRNAs are significantly associated with tumor development and metastasis (Liu et al, 2019;Wang et al, 2019;Chen et al, 2021;Zhang and Liu, 2021;Cao et al, 2022). Compared with normal tissues, miRNA expression is down-regulated in various cancers.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) belong to a family of non-coding RNAs of 20-24 nucleotides in length. MiRNAs are significantly associated with tumor development and metastasis (Liu et al, 2019;Wang et al, 2019;Chen et al, 2021;Zhang and Liu, 2021;Cao et al, 2022). Compared with normal tissues, miRNA expression is down-regulated in various cancers.…”
Section: Discussionmentioning
confidence: 99%
“…85,86 One confirmed that high glucose levels inhibited TDSC proliferation and differentiation through the let-7b-5p/CFTR pathway, contributing to poor tendon healing in patients with DM (Figure 2A). 87 Under the high glucose levels present in cases of DM, CFTR may adversely impact TDSCs and consequently affect tendon healing. Hence, further analysis of the interplay between CFTR and TDSCs can provide novel insights into tendon biology and disease mechanisms, as well as new strategies for the treatment and regeneration of tendons following injury events.…”
Section: Dovepressmentioning
confidence: 99%
“…Diabetic rats have increased rotator cuff fatty infiltration, poor biomechanics ( 5 ), and accelerated steatosis after rotator cuff injury ( 4 ). In addition, the detrimental effects of diabetes persist even after the repair of rotator cuff injury, and persistent hyperglycemia impairs tendon-to-bone healing after rotator cuff repair in a rat model, resulting in worse biomechanics and histology ( 6 ), which may be associated with the let-7b-5p/CFTR pathway ( 7 ). However, whether this leads to poor biomechanics is still controversial.…”
Section: Introductionmentioning
confidence: 99%